PENINGKATAN ADVERSITY QUOTIENT (AQ) MELALUI KEGIATAN KEPRAMUKAAN DAN SELF EFFICACY PADA SISWA SMA SURAKARTA - Endang Widyastuti; Yustinus Joko Dwi Nugroho (Jurnal Psikohumanika, 2016)
One of the objectives of national education is establishing a formidable human being and character. Adversity quotient is one of the determinants to achieve that aim. Adversity Quotient is the ability, toughness and high fighting spirit at the time met difficulty. Self-confidence, that is known as self-efficacy, and scouts are capable of supporting the increasing ability of adversity quotient of high school students that are expected to form a human character. This study aimed to determine the level of adversity quotient, the role of scout and efficacy for the increased of adversity quotient on high school students in Surakarta. It also purposes to see the difference Adversity Quotient (AQ) among students who take with students who do not take the scouting. The respondent in this study are 245 the high school students, taken from high schools and vocational schools in Surakarta. Determination of the sample used random cluster sampling technique. Scale was used to collecting data, consists of self-efficacy scale and adversity quotient scale. The results showed that there was a significant positive correlation between self-efficacy with adversity quotient, indicated by it’s correlation coefficient (r = 0.789; p = 0.000). The results of different test against a group of students who attend and not atend the scouts showed that there was no difference in adversity quotient between the two groups.